2015
DOI: 10.1083/jcb.201412111
|View full text |Cite
|
Sign up to set email alerts
|

The Msd1–Wdr8–Pkl1 complex anchors microtubule minus ends to fission yeast spindle pole bodies

Abstract: Msd1–Wdr8 are delivered by Pkl1 to mitotic spindle pole bodies, where the Msd1–Wdr8–Pkl1 complex anchors the minus ends of spindle microtubules and antagonizes the outward-pushing forces generated by Cut7/kinesin-5 in fission yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
99
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(116 citation statements)
references
References 84 publications
15
99
1
1
Order By: Relevance
“…Interestingly, orthologues of SSX2IP and WDR8 have been found in conserved complexes not only in human cells, as shown here, but previously in Aspergillus nidulans (Shen and Osmani, 2013), in Schizosaccharomyces pombe (Toya et al, 2007;Yukawa et al, 2015) and X. laevis (O.G., unpublished observation). This indicates that the SSX2IP-WDR8 protein module must be highly conserved throughout eukaryotic evolution.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Interestingly, orthologues of SSX2IP and WDR8 have been found in conserved complexes not only in human cells, as shown here, but previously in Aspergillus nidulans (Shen and Osmani, 2013), in Schizosaccharomyces pombe (Toya et al, 2007;Yukawa et al, 2015) and X. laevis (O.G., unpublished observation). This indicates that the SSX2IP-WDR8 protein module must be highly conserved throughout eukaryotic evolution.…”
Section: Discussionmentioning
confidence: 58%
“…Here, we have identified human WDR8 (also known as WRAP73) as an interacting partner of the satellite components SSX2IP and PCM1 (Shen and Osmani, 2013;Yukawa et al, 2015). We show that, in contrast to SSX2IP and PCM1, which only associate with cytoplasmic satellite complexes, a large fraction of WDR8 localises to centrioles and basal bodies even when satellites are dispersed.…”
Section: Introductionmentioning
confidence: 97%
“…For example, it has been reported that overexpression of Ned1 (11) (a protein known to influence the stability of chromosome) or Mia1 (12), deletion of Msd1 (13), or malfunction of the Msd1-Wdr8-Pkl1 complex (14) and the knockout of pkl1 (15), all induce improper anchoring of MTs to the SPBs, resulting in panhandle-shaped protrusions of NE driven by elongating microtubule bundles. Similar effect can also be achieved by the abscission of SPBs using laser microsurgery (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…2D). In the mitotic spindle pole body, Pkl1 is required for the localization of Msd1 and the mitosis-specific spindle pole body component Wdr8; it cooperatively interacts with these two proteins to mediate the spindle anchoring, where it counteracts the outward pushing forces that are generated by Cut7 (Yukawa et al, 2015). In addition, Pkl1 also functions as the spindle assembly checkpoint, which regulates chromosome bi-orientation by mediating the spindle pole assembly (Grishchuk et al, 2007).…”
Section: Tug-of-war Between Kinesin-14 and Kinesin-5 In Spindle Assemblymentioning
confidence: 99%
“…First, kinesin-14 motors have the intrinsic ability to focus the minus-ends of microtubules into spindle poles, but kinesin-5 motors counteract focusing of the microtubule plus-ends at the poles (Hentrich and Surrey, 2010). Second, kinesin-14 motors generate inward pulling forces on spindles, whereas the kinesin-5 motors have been shown to generate outwards forces on spindles in vitro (Yukawa et al, 2015). Another mechanism by which kinesin-14 and kinesin-5 counterbalance their activities does not require the motor domains but is mediated primarily by the tail, i.e.…”
Section: Box 2 Microtubule End-binding Proteins and Plus-end Trackingmentioning
confidence: 99%